Associação entre bioinseticidas comerciais a base de fungos sobre Euschistus heros Fabricius, 1798 (Hemiptera: Pentatomidae) - Quisini, Renan (2022)
The soybean crop is produced under different types of management and, regardless of them, it is affected by insect pests that cause significant losses in cultivation. Sucking insects, especially Euschistus heros Fabricius, 1798 (Hemiptera: Pentatomidae), have great potential to cause damage, due to the high population rate and the damage to the commercial product. In addition, the difficulty of controlling this pest is added, due to the natural characteristics of the species and low rotation of modes of action of synthetic chemical insecticides, which lead to the selection of naturally tolerant individuals, which certainly represent a problem in the medium and long term. In view of the demand for information from the agricultural sector, as well as the development of technologies with less environmental impact, this work proposes to evaluate the effect of commercial bioinsecticides based on Metarhizium anisopliae, Isaria fumosorosea and Beauveria bassiana individually and in association on E. heros, under laboratory conditions. The commercial bioinsecticides used and their active principles were: MetaTurbo® (M. anisopliae), BovériaTurbo® (B. bassiana) and Octane® (I. fumosorosea), respectively at doses: 1.5 Kg.ha1, 1 Kg.ha1 and 1 L.ha1. The treatments consisted of individual and associated application of fungibased bioinsecticides, in a spray volume of 200L.ha1. Each treatment was sprayed, with the aid of an airbrush and a pressure pump, on third instar nymphs and adults of E. heros. Five replications (plates) were used, with 15 bugs each, in a completely randomized design. The bugs were kept in an acclimatized environment at a temperature of 25 ± 2oC, relative humidity of 60 ± 5% and a photoperiod of 12 hours. The evaluations took place daily, for a period of 10 days after application, quantifying the dead. Oviposition and weight of adult insects surviving from the application of treatments in 3rd instar were also evaluated, as well as the hatching of nymphs from eggs. It was verified that the treatments Bometil®, BovériaTurbo® + MetaTurbo® + Octane® stood out, causing mortality of third instar nymphs, respectively, of 64.00 and 62.66%. For adult bed bugs, there was no difference between treatments. Regarding sublethal effects, there was no significant difference between treatments. The combinations of bioinsecticides based on entomopathogenic fungi show promise in the management of E. heros, especially for third instar E. heros nymphs under laboratory conditions. Studies under field conditions are necessary to evaluate the efficiency in the field.